Neuroendoscopy Combined with Intraoperative Low-Field Magnetic Imaging for Treatment of Multiloculated Hydrocephalus in a 7-Month-Old Infant: Technical Case Report - Tabakow, P.; Czyz, M.; Jarmundowicz, W.; Zub, W. (min - Minimally Invasive Neurosurgery, 2011)
Treatment of multiloculated hydrocephalus in children remains a difficult neurosurgical problem because of the high recurrence rate. Endoscopic septostomy with subsequent ventriculoperitoneal shunting is one of the most widely accepted therapeutic methods. Intraventricular endoscopic surgery combined with intraoperative magnetic resonance (MR) has been used very seldom in infants.A 7-month-old infant presented with a history of postnatal hydrocephalus from the germinal matrix and intraventricular hemorrhage, treated with a ventriculoperitoneal shunt. Treatment was complicated by bacterial meningitis. On admission the child presented with symptoms of elevated intracranial pressure, an MR investigation gave evidence of multiloculated hydrocephalus. The patient underwent endoscopic pellucidotomy, followed by fenestration of the septa inside the third ventricle, third ventriculostomy and aqueductoplasty. Endoscopic navigation was supported by serial intraoperative non-contrast T1-weighted MR (0.15 T, Polestar N20, Medtronic) images. They also served for confirmation of the patency of performed fenestrations and for the planning of further steps of the operation.Intraoperative low-field MR imaging provided an excellent tool for correct navigation of the endoscope inside the pathological ventricular compartments and for intraoperative assessment of surgical goals.
Keywords: endoscopy; hydrocephalus; ventriculostomy; MRI; intraoperative imaging